Эцэг эхээ үзэх монгол, япон хүний сэтгэлгээний онцлог: Characteristics of Mongolian and Japanese attitudes towards parents - Д., Дэлгэрсүрэн (Mongolian Studies, 2023)
There are many previous studies about the concept for the parents of Japanese and Mongolian children. However, side-by-side comparisons studies show that on the national characters of the two people, discussed in the terms of cultural studies and sociolinguistics sayings about the parents in particular, have not been touched too much. Therefore, how the culture behind it and the features of the concept of the parents of the two countries, clarify the point at which the expression forms of the proverb about the parents of Japanese and Mongolian, similarities and differences, are expressed in the proverb of the comparisons. I thought if I’ve understand, and would like to consider.